Evidence Update for Minimally Invasive Surgical Evacuation of Supratentorial Spontaneous Intracerebral Hemorrhage: A Science Advisory From the American Heart Association - Stacey Q. Wolfe; Sepideh Amin-Hanjani; Christine Tschoe; Scott D. Simon; Christopher P. Kellner; Kevin N. Sheth (Stroke, 2026)
Recent evidence has reignited interest in the role of surgical intervention for improving outcomes after spontaneous intracerebral hemorrhage. Historically, the surgical management of intracerebral hemorrhage has been limited due to concerns regarding procedural risks and lack of functional improvement. However, recent advances in minimally invasive surgical techniques suggest improvements in functional recovery, broadening consideration for surgical treatment of certain patients, such as those with lobar hemorrhage after spontaneous intracerebral hemorrhage. This science advisory summarizes randomized evidence for minimally invasive surgical evacuation of intracerebral hemorrhage compared with medical management, including considerations related to patient selection, care pathways, and surgical technique.